مؤشرات التنمية المستقلة في الاقتصاد السوري - صيوح لؤي محمد (Latakia University Journal - Economic and Legal Sciences Series, 2013)
انعكست الأزمات الأخيرة التي تعرض لها الاقتصاد العالمي بتداعيات على مختلف اقتصادات دول العالم حسب درجة ارتباطها به، ودمرت المكاسب الاقتصادية لبعض الدول العربية التي تم تحقيقها نتيجة للانفتاح الاقتصادي غير المدروس غافلين دور التنمية المستقلة بغض النظر عن مدى فاعليتها في بعض الاقتصادات الوطنية المعتمدة على الذات بالإمكانيات المتاحة، لذلك وبغض النظر عن الجهة التي كانت وراء تلك الأحداث والأسباب والدوافع الكامنة وراءها إلا أنها فرضت واقعا جديداً يحتم تغير التوجهات والإستراتيجيات التي تحدد الخطط التي يجب السير عليها لمعالجة المشكلات الاقتصادية والاجتماعية في أي بلد، فالاقتصاد السوري يعاني من مجموعة من الاختلالات الاقتصادية نتيجة السياسات الاقتصادية المطبقة خلال السنوات السابقة وهو ماترتبت عليه آثار سلبية على مسارات التنمية في سورية، لقد تحول الاقتصاد السوري تدريجياٌ الى اقتصاد ريعي يقوم على المضاربات العقارية والمالية وتراجعت القطاعات المنتجة الزراعية والصناعية تراجعاً ملموساً وهو ما أسفر عن تزايد الانكشاف على الخارج الى مستويات خطيرة. كما أدى الى مزيد من البطالة والفقر والتهميش الاقتصادي والاجتماعي لفئات واسعة من سكان سورية. لذلك سيناقش هذا البحث مؤشرات التنمية المستقلة في الاقتصاد السوري، وذلك من خلال دراسة وتحليل أهم هذه المؤشرات المتمثلة بخمس مؤشرات رئيسة: المؤشر الأول هو فجوة الموارد الداخلية (فجوة الادخار والاستثمار)، والثاني هو فجوة الموارد الخارجية ( الفجوة بين الصادرات والواردات)، والثالث هو مؤشر الدين الخارجي، والرابع هو مؤشر الأمن الغذائي، والخامس هو مؤشر العلاقات الخارجية، وصولاً إلى تحديد النتائج ووضع بعض التوصيات التي تفيد في معالجة معوقات التنمية المستقلة للاقتصاد السوري. The latest crises, which global economy has undergone by, have had repercussions on the various economies in the world depending on how connected they are to it. Economic gains of some Arab countries resulting from unstudied open economy have been undermined, overlooking the role of independent development regardless of how efficient it is in some self-dependent national economies with the available capabilities. Therefore, regardless of who is responsible for these happenings and the reasons and motives underlying them, they have imposed a new reality that necessitates a change of directions and strategies that define the plans which should be followed to deal with economic and social problems in any country. Syrian economy suffers a number of economic flaws as a result of economic policies implemented during the past years. This has affected the course of development in Syria. Syrian economy has gradually turned into a reneconomy that is based into financial and real-estate ventures. Production sectors, agricultural and industrial, have significantly declined. This has led to dangerous exposition on the outside. It also led to more unemployment, poverty, and social and economic negligence for vast groups of Syrian population. This research will, therefore, discuss the indicators of independent development in Syrian Economy through examining and analyzing the five major indicators; the first one is the gap in internal resources (the gap of investment and reserve), the second is the gap in external resources (the gap between exports and imports), the third is external debt, the fourth is food security and the fifth is foreign relations. This leads to identifying the results and putting forward some recommendations that help in getting over the obstacles hindering independent development in Syrian Economy.